2020
DOI: 10.1111/imj.14332
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year follow up of adrenal incidentalomas in a New Zealand centre

Abstract: Background The international guidelines for management of adrenal incidentalomas (AI) are becoming more conservative. These changes are based on the growing body of evidence suggesting that non‐functioning adenomas have a low likelihood of becoming functional or malignant over time. Aims To follow up at least 100 patients for 3 years who were originally found to have benign adrenal adenomas which were non‐functional or had subclinical Cushing syndrome (SCS). Methods This study prospectively evaluated consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Nine patients had evidence of ACS at diagnosis (defined as an elevated 24-hour UFC and a 1mg-DST), while the remaining 92 patients were diagnosed with a nonfunctioning AI. At 3 years, 5 of the 9 patients with ACS at diagnosis (44%) showed normalization of cortisol parameters, while 5 of the 92 patients with a nonfunctional AI developed ACS (5%) ( 268 ). Barzon et al reported the cumulative incidence of ACS after 1and 5 years as 3.8% and 6.6%, respectively ( 68 ).…”
Section: Endocrine Work-up Of Aimentioning
confidence: 99%
“…Nine patients had evidence of ACS at diagnosis (defined as an elevated 24-hour UFC and a 1mg-DST), while the remaining 92 patients were diagnosed with a nonfunctioning AI. At 3 years, 5 of the 9 patients with ACS at diagnosis (44%) showed normalization of cortisol parameters, while 5 of the 92 patients with a nonfunctional AI developed ACS (5%) ( 268 ). Barzon et al reported the cumulative incidence of ACS after 1and 5 years as 3.8% and 6.6%, respectively ( 68 ).…”
Section: Endocrine Work-up Of Aimentioning
confidence: 99%
“…Taking into account that the main consequences of subclinical hypercortisolism are arterial hypertension, metabolic disorders and diabetes, the New Zealand group coordinated by Goh et al suggests to evaluate case by case before engaging in too many investigations and wasting unnecessary resources [109]. We must keep in mind that in ACS the cortisol-related comorbidities, such as cardiovascular risk factors, impaired glucose or lipid metabolism, bone disease and the impaired quality of life [62,[110][111][112][113][114][115], are related to modest changes of cortisol secretion.…”
Section: Question 3: Is Surgery An Appropriate Treatment In Patients With Acs?mentioning
confidence: 99%
“…At the beginning of the study nine cases showed signs of cortisol excess. At 3 years, five of the nine cases of hyperfunction normalized, while the other five showed a subclinical cortisol secretion (5%) [ 109 ].…”
Section: Question 4: Can a Non-functioning Lesion Become Acs And A Benign Adenoma Become Malignant?mentioning
confidence: 99%
“…A consistent cohort of patients present a subclinical autonomous cortisol secretion (ACS), without the full-blown clinical picture of overt hypercortisolism (6,7). Several studies reported a progression from a nonfunctioning adrenal incidentaloma (NFAI) to ACS in up to 11% of cases (8)(9)(10), especially in larger adenomas (11,12).…”
Section: Introductionmentioning
confidence: 99%